Hydromagnetic Squeeze Film in Rough Porous Narrow Journal Bearing: A Study of Slip Effect - Snehal Shukla; Gunamani Deheri (Tribology Online, 2017)
This article aims to study the influence of slip on a hydromagnetic squeeze film in transversely rough porous narrow journal bearing. The Neuringer-Rosensweig model governs the fluid flow. The slip model of the Beavers and Joseph has been used. The stochastic modeling of Christensen and Tonder has been adopted for calculating the effect of transverse surface roughness. The pressure distribution is obtained by solving the concerned stochastically averaged Reynolds type equation. It is observed that the adverse effect of roughness gets compounded due to slip effect. Equally is the crucial role of eccentricity for the performance of a bearing system. The results confirm that slip has to be at minimum for any improvement in the performance. Besides, the absence of flow does not deter the system from supporting a good amount of load which does not happen in the case of a traditional lubricant.